2017
DOI: 10.1186/s12890-017-0468-5
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in the treatment of idiopathic pulmonary fibrosis―insights from patient chart review in five European countries

Abstract: BackgroundTwo antifibrotic drugs, pirfenidone and nintedanib, are approved by the European Medicines Agency and the US Food and Drug Administration for the treatment of idiopathic pulmonary fibrosis (IPF). In this analysis, treatment patterns of European patients with IPF were investigated to understand antifibrotic prescribing and identify unmet needs in IPF treatment practice.MethodsBetween February and March 2016, respiratory physicians from France, Germany, Italy, Spain, and the UK participated in an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 44 publications
5
77
1
Order By: Relevance
“…Data from our physician survey suggested that 25-50% of patients with progressive fibrosing ILDs did not receive any drug therapy in the past year. These findings are in line with data from an online survey of 290 European physicians managing patients with IPF conducted in February-March 2016 that indicated that 54% of patients with IPF, and 71% of those with IPF considered to be mild, were not treated with an approved antifibrotic agent 38 . Approximately a third of the pulmonologists and nearly half of the rheumatologists included in our online survey indicated that a primary reason for not initiating therapy in patients with progressive fibrosing ILDs was that patients were considered to have a "mild" level of disease.…”
Section: Discussionsupporting
confidence: 87%
“…Data from our physician survey suggested that 25-50% of patients with progressive fibrosing ILDs did not receive any drug therapy in the past year. These findings are in line with data from an online survey of 290 European physicians managing patients with IPF conducted in February-March 2016 that indicated that 54% of patients with IPF, and 71% of those with IPF considered to be mild, were not treated with an approved antifibrotic agent 38 . Approximately a third of the pulmonologists and nearly half of the rheumatologists included in our online survey indicated that a primary reason for not initiating therapy in patients with progressive fibrosing ILDs was that patients were considered to have a "mild" level of disease.…”
Section: Discussionsupporting
confidence: 87%
“…Recent evidence from post hoc analyses supports early initiation of antifibrotic therapy once patients have been diagnosed with IPF to reduce loss of lung function and slow disease progression [15][16][17][18]. However, despite the availability of effective treatments, ∼40% of patients with a confirmed diagnosis of IPF do not receive treatment [19].…”
Section: Introductionmentioning
confidence: 99%
“…Real-world data suggest that many patients are not treated with approved IPF therapies immediately after diagnosis, despite the insidious, progressive nature of IPF. In a 2016 European patient chart survey, 53.6% of patients with IPF (N = 1783) were not treated with nintedanib or pirfenidone [36]. A retrospective review of Finnish (n = 158) and Swedish (n = 174) patients with IPF found that, from 2014 to 2016, 45 (29.6%) Finnish and 111 (69.4%) Swedish patients were prescribed nintedanib or pirfenidone [37].…”
Section: When To Initiate Treatmentmentioning
confidence: 99%